2020
DOI: 10.7249/rr2088-1
|View full text |Cite
|
Sign up to set email alerts
|

The Science of Gun Policy: A Critical Synthesis of Research Evidence on the Effects of Gun Policies in the United States, Second Edition

Abstract: INITIATIVE Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 132 publications
1
52
0
Order By: Relevance
“…8,31 Overall, the effects of these laws on suicide rates are inconclusive. [8][9][10][31][32][33] The majority of these studies focused on suicide mortality in the youngest age groups (<21 years of age) and did not investigate effects at the individual level, however, thereby precluding the ability to account for actual access and use of rearms during childhood at the person level and the possibility for delayed effects across the lifespan. Person-level analyses may therefore provide novel information about how rearm availability and suicide risk are related, thereby complementing previous research, the majority of which has examined aggregate correlations.…”
Section: Discussionmentioning
confidence: 99%
“…8,31 Overall, the effects of these laws on suicide rates are inconclusive. [8][9][10][31][32][33] The majority of these studies focused on suicide mortality in the youngest age groups (<21 years of age) and did not investigate effects at the individual level, however, thereby precluding the ability to account for actual access and use of rearms during childhood at the person level and the possibility for delayed effects across the lifespan. Person-level analyses may therefore provide novel information about how rearm availability and suicide risk are related, thereby complementing previous research, the majority of which has examined aggregate correlations.…”
Section: Discussionmentioning
confidence: 99%
“…A RAND survey of the evidence for CAP laws found that CAP laws may decrease the risk of unintentional injury and death in children. 7 Policymakers are urged to expand safe storage laws, which require that firearms be stored unloaded and locked, and CAP laws, which place liability on adults who permit youth to have access to a firearm without supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effects of gun laws that rely on cross-sectional designs or simple longitudinal designs (without a control group) would therefore not be classified as difference-in-difference designs. In their comprehensive review of the literature on the effects of gun policy, Smart et al (2020) rely on this criterion to identify the studies summarized in their review as they believe that such designs provide the strongest evidence of causal effects.…”
Section: Gun Laws and Youth Suicide By Firearm: The Evidencementioning
confidence: 99%
“…Although there is a large literature on the effects of gun laws on various measures of violent crime, far fewer studies have examined the effects of gun laws on suicide and even fewer focus on youth suicide rates (Smart et al, 2020). The literature on youth suicide by firearm has largely focused on two types of gun laws, both of which are designed to limit youth access to guns.…”
Section: Gun Laws and Youth Suicide By Firearm: The Evidencementioning
confidence: 99%